The effectiveness of applying modern technology in enhancing financial management and budget in the Ministry of Health - Jazan Health Cluster - Mansour Abdo Ahmed Alsaadi, (International Journal of Computers and Informatics, 2024)
This study aims to measure the effectiveness of applying modern technology in enhancing financial management and budgeting in the Ministry of Health, especially in Jazan Health Cluster, by analyzing the impact of using technology in improving financial operations such as reducing time, reducing human errors, increasing the accuracy of financial reports, and enhancing the integration of financial systems. The study followed the quantitative methodology in data analysis, as data was collected from a sample of 165 participants working in the financial administration of the Ministry of Health. Using statistical analysis tools such as one-way analysis of variance (ANOVA) and Bayes Factor test, the results showed that there is a positive and noticeable impact of using modern technology in improving financial efficiency by reducing time and errors, and increasing the accuracy of financial reports. The results also showed that the integration of financial systems enhances the effectiveness of administrative work. Based on these results, the study recommended the need to enhance the use of technology in financial operations, develop training for human cadres, enhance the integration of financial systems, and achieve a higher level of financial transparency.
Keywords: Modern Technology; Financial Management; Budget; Ministry of Health, Jazan